2020
DOI: 10.1089/ten.tea.2019.0199
|View full text |Cite
|
Sign up to set email alerts
|

Silk-Reinforced Collagen Hydrogels with Raised Multiscale Stiffness for Mesenchymal Cells 3D Culture

Abstract: Type I collagen hydrogels are of high interest in tissue engineering. With the evolution of 3D bioprinting technologies, a high number of collagen-based scaffolds have been reported for the development of 3D cell cultures. A recent proposal was to mix collagen with silk fibroin derived from Bombyx mori silkworm. Nevertheless, due to the difficulties in the preparation and the characteristics of the protein, several problems such as phase separation and collagen denaturation appear during the procedure. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 85 publications
2
31
0
Order By: Relevance
“…We focused our analysis on the extrusion-based bioprinting of an MSC-laden collagen 3D scaffold, a process that is currently under development in our lab for potential future applications in the regeneration of cartilage. We chose a standalone collagen bioink, despite the fact that combination with different materials has been generally considered to improve printability [31][32][33][34]. In parallel, we selected a population of solely human MSCs from bone marrow and not a mixture (i.e., MSCs and chondrocytes), which would better foster regenerative processes in the articular microenvironment [35].…”
Section: Discussionmentioning
confidence: 99%
“…We focused our analysis on the extrusion-based bioprinting of an MSC-laden collagen 3D scaffold, a process that is currently under development in our lab for potential future applications in the regeneration of cartilage. We chose a standalone collagen bioink, despite the fact that combination with different materials has been generally considered to improve printability [31][32][33][34]. In parallel, we selected a population of solely human MSCs from bone marrow and not a mixture (i.e., MSCs and chondrocytes), which would better foster regenerative processes in the articular microenvironment [35].…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogel properties both had matched biomechanical properties and contained ECM instructive factors from the native lung tissue (De Santis et al, 2020). Hydrogels based on collagen type I, one of the major structural components of tissues, has been extensively explored in combination with other materials such as silk, a highly elastic protein, to improve the mechanical properties to mimic the viscoelastic properties of tissues (Sanz-Fraile et al, 2020). As discussed above, GAGs multiple functions in cell signaling and in tissue homeostasis and have been explored as biomaterials.…”
Section: Hydrogel Encapsulationmentioning
confidence: 99%
“…One study found that silk‐reinforced collagen hydrogels had excellent mechanical properties with a maximum elastic modulus of up to 31 kPa and the stress of up to 1.8 kPa, matching with the native ventricular muscle (elastic modulus of 20 kPa, stress of 4 kPa). [ 52 ] Compared to the cells cultured within soft collagen hydrogels, BM‐derived mesenchymal stem cells (BMSCs) cultured within the silk‐reinforced hydrogels had more elongated morphology and were more evenly distributed. The topographical characteristic, another physical property of the scaffold, can affect the adhesion, alignment, morphology, and size of CMs.…”
Section: Tissue Engineering Therapy Currently Used To Treat Heart Dismentioning
confidence: 99%
“…And the stiffness was close to normal heart tissue, which was beneficial for the utilization of CTE. [ 52 ]…”
Section: Silk Protein For Ctementioning
confidence: 99%